The Use of Aerial Drone Technology for Landslide Investigation in Nickel Mining PT. KLM - Baehaqi, Hendy; Umniyati, Yunita; Galinium, Maulahikmah (Dinasti Research, 2025)
This study explores the use of drone technology to assess landslides within PT. KLM’s nickel mining area. Key challenges in collecting geotechnical data include difficult terrain, landslide risks, and limitations of conventional survey methods. The research applies the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) approach to identify issues, collect and analyze drone data, and develop solutions to reduce landslide risks. Drone flights were conducted at altitudes of 100 m, 150 m, and 200 m, producing maps that evaluate each flight's image resolution, collision risk, photo coverage, flight area, and suitability. Based on these results, the 150 m altitude was selected as optimal. Using Real Time Kinematic (RTK) processing, the drone data showed an average accuracy variance of about 0.317 meters. Findings indicate that drone data effectively produces high-resolution orthophotos, contour maps, and 3D models to monitor terrain changes before and after landslides. Overall, drone technology improves efficiency, enhances safety, and increases data quality for better landslide risk management in nickel mining.